2012
DOI: 10.1002/adma.201104241
|View full text |Cite
|
Sign up to set email alerts
|

Janus Au‐TiO2 Photocatalysts with Strong Localization of Plasmonic Near‐Fields for Efficient Visible‐Light Hydrogen Generation

Abstract: The first use of non-centrosymmetric Janus Au-TiO(2) photocatalysts in efficient, plasmon-enhanced visible-light hydrogen generation is demonstrated. The intense localization of plasmonic near-fields close to the Au-TiO(2) interface, coupled with optical transitions involving localized electronic states in amorphous TiO(2) brings about enhanced optical absorption and the generation of electron-hole pairs for photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
604
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 806 publications
(621 citation statements)
references
References 52 publications
17
604
0
Order By: Relevance
“…At 0.5 h, the UV-vis spectrum exhibits a strong visible light absorption at 520 nm, indicating the formation of Au nanocrystals. 43 When the reaction time increased to 1 h, the absorption peak at 520 nm increased accordingly, indicating the growth of Au nanocrystals. At 2 h, the absorption peak of Au became weaker as a result of the deposition of Rh on the surfaces of the Au nanocrystals.…”
Section: Bimetallic Aurh Nanodendrites Y Kang Et Almentioning
confidence: 97%
“…At 0.5 h, the UV-vis spectrum exhibits a strong visible light absorption at 520 nm, indicating the formation of Au nanocrystals. 43 When the reaction time increased to 1 h, the absorption peak at 520 nm increased accordingly, indicating the growth of Au nanocrystals. At 2 h, the absorption peak of Au became weaker as a result of the deposition of Rh on the surfaces of the Au nanocrystals.…”
Section: Bimetallic Aurh Nanodendrites Y Kang Et Almentioning
confidence: 97%
“…Seh et al also reported the enhanced photocatalytic activity via the strong localization of plasmonic near fields in Janus Au/TiO 2 nanostructures with uniform size of Au nanoparticles ranging from 30 to 70 nm, which were found to outperform those using 5 nm Au nanoparticles with a 4–7 fold increase in hydrogen generation under visible light irradiation 45. The disparity in photocatalytic activity is attributed to the stronger plasmonic near‐field enhancements and optical absorption enhancements of the larger Au nanoparticles in greater contact with TiO 2 nanoparticles ( Figure 6 ).…”
Section: Photocatalytic Water Splittingmentioning
confidence: 98%
“…Ongoing research aims for efficient low-temperature catalysis at ambient conditions, to reduce unwanted side reactions and prolong catalyst lifetime. Plasmon-induced catalysis promises to achieve these goals: in recent years, research groups have demonstrated, e.g., plasmon-driven H 2 production from alcohol [2,3], liquid-phase water splitting [4][5][6], gas-phase oxidation reactions [7,8], and hydrocarbon conversion [9]. In particular, noble-metal nanoparticles comprise an excellent source of hot electrons [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%